Premedication with pregabalin 150mg versus 300mg for postoperative pain relief after laparoscopic cholecystectomy - Tanveer Singh; Suneet Kathuria; Richa Jain; Dinesh Sood; Shikha Gupta (Wolters Kluwer Medknow Publications, 2020)
Background and Aims: Pregabalin has been used in various studies for postoperative pain relief in varying doses. However, there is no conclusive evidence to support a safe and effective dose of pregabalin. The present study was designed to compare the efficacy of two different preoperative doses of pregabalin (150 mg and 300mg) in patients undergoing laparoscopic cholecystectomy for postoperative pain relief. Material and Methods: Ninety adult patients of either sex with American Society of Anesthesiologist physical status I and II scheduled for elective laparoscopic cholecystectomy under general anesthesia were randomized to receive pregabalin 150mg (group A), pregabalin 300mg (group B), or placebo (group C) orally 1 h before surgery. The pain was assessed using a visual analog scale (VAS) and a verbal rating scale (VRS) for the initial 24 h postoperatively. The primary outcome of our study was the comparative assessment of the severity of pain in the postoperative period in three groups. Postoperative analgesic consumption and incidence of side effects were assessed as secondary outcome measures. Results: VAS score was significantly more in group C than group A and B (P-value <0.05). The total amount of fentanyl required in 24 h was least in group B (228.33 ± 42.41μg) followed by group A (292.50 ± 46.49μg) and group C (322.50 ± 39.58μg) (P-value 0.0001). The incidence of sedation, dizziness, and visual disturbances was more in group B as compared to group A and was least in group C. Conclusions: Pregabalin 150 mg is effective in decreasing postoperative pain after laparoscopic cholecystectomy with fewer incidences of adverse effects such as sedation and visual disturbances as compared to pregabalin 300 mg.